2013
DOI: 10.1177/1534765612445931
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the completion of trauma-focused treatments: What can make a difference?

Abstract: This study expands our understanding of treatment attrition by investigating factors predicting treatment dropout in a large national data set of clinic-referred children and parents seeking trauma-specific psychotherapy services. Using de-identifed data (N = 2,579) generated by the National Child Traumatic Stress Network Core Data Set collected between spring 2004 and fall 2010, the study uses sequential logistic regression analyses to assess prediction of the probability of a given subject having prematurely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
52
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 55 publications
(64 reference statements)
6
52
1
Order By: Relevance
“…Child age and gender were not associated with clinician‐rated treatment completion. These findings are in line with most of the prior research in this area, which has not observed associations between attrition and age (Sprang et al., 2013; Yaskini et al., 2018) or gender (Celano et al., 2018; Sprang et al., 2013; Wamser‐Nanney & Steinzor, 2016, 2017; Yasinski et al., 2018). However, some prior studies with mostly school‐aged children have reported that younger child age may be a protective factor against dropout (Fraynt et al., 2014; Wamser‐Nanney & Steinzor, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Child age and gender were not associated with clinician‐rated treatment completion. These findings are in line with most of the prior research in this area, which has not observed associations between attrition and age (Sprang et al., 2013; Yaskini et al., 2018) or gender (Celano et al., 2018; Sprang et al., 2013; Wamser‐Nanney & Steinzor, 2016, 2017; Yasinski et al., 2018). However, some prior studies with mostly school‐aged children have reported that younger child age may be a protective factor against dropout (Fraynt et al., 2014; Wamser‐Nanney & Steinzor, 2016).…”
Section: Discussionsupporting
confidence: 90%
“…However, some prior studies with mostly school‐aged children have reported that younger child age may be a protective factor against dropout (Fraynt et al., 2014; Wamser‐Nanney & Steinzor, 2016). Minority status was a risk factor for clinician‐rated attrition, which is consistent with other studies of mostly school‐aged children and adolescents (Fraynt et al., 2014; Murphy et al., 2014; Sprang et al., 2013; Wamser‐Nanney & Steinzor, 2016). This may be a function of minority families having additional stressors and burdens or it may be due to negative perceptions among various racial and ethnic groups regarding treatment.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Several studies have shown that dropout is a common problem in youth trauma treatments (Gopalan et al, 2010;Lau & Weisz, 2003). So far, the majority of studies of dropout in youth PTSD treatments have investigated youth background and demographic variables; less attention has been paid to the in-treatment process variables (Chasson, Vincent, & Harris, 2008;Eslinger, Sprang, & Otis, 2012;Sprang et al, 2013). In particular, both youth-therapist and caregiver-therapist alliances hold promise as important predictors of dropout.…”
Section: Tables and Figuresmentioning
confidence: 99%
“…Treatment dropout in child mental health is a pressing dilemma. It has been estimated that up to 80% of families drop out prematurely from interventions, indicating attention must be directed to address families' practical problems with attending therapy as well as their issues with the relevance of the treatment process (Ingoldsby, 2010;Sprang et al, 2013). Interestingly, C/A nurses' evidence-based yet practical approach might provide an excellent avenue for tailoring family-centered interventions that decrease attrition (Saxe, Heidi Ellis, Fogler, & Navalta, 2012).…”
mentioning
confidence: 99%